2014
DOI: 10.1080/13678868.2014.896129
|View full text |Cite
|
Sign up to set email alerts
|

The same but different: HRD master’s programmes in the United States

Abstract: In this study, we examined the curricular and institutional characteristics of HRD master's programmes in the United States. Our sample included 108 programmes in 100 institutions that were self-identified as HRD programmes. Among our findings: (1) fewer programmes were located in schools of education (44%) and more were located in schools of business (28%) than indicated by previous research; (2) there was greater homogeneity in curriculum among programmes in the same institutional locations (e.g. schools of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…However, some in the CRT community have argued for the use of survey, quantitative, and mixed methods approaches to constructing counterstories (DeCuir‐Gunby & Walker‐DeVose, ). We used qualitative surveys in our study to allow for the emergence of stories that countered the dominant narrative of blindness toward racism and other forms of social injustice in recent curricular research in HRD (Lim & Rager, ; Lim, Song, Choi, & Kim, ; Zachmeier, Cho, & Kim, ). Simultaneously, we hoped to learn more about the teaching and learning of critical theories used to confront injustice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some in the CRT community have argued for the use of survey, quantitative, and mixed methods approaches to constructing counterstories (DeCuir‐Gunby & Walker‐DeVose, ). We used qualitative surveys in our study to allow for the emergence of stories that countered the dominant narrative of blindness toward racism and other forms of social injustice in recent curricular research in HRD (Lim & Rager, ; Lim, Song, Choi, & Kim, ; Zachmeier, Cho, & Kim, ). Simultaneously, we hoped to learn more about the teaching and learning of critical theories used to confront injustice.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite calls for research into how critical and social justice themes are taught in Human Resource Development (HRD) programs (Byrd, ), the current literature tells us little about how future scholars and practitioners are being prepared to face workplace injustice. Despite the fact that over 17 percent of Academy of Human Resource Development (AHRD) members are affiliated with the Critical HRD (CHRD) and Social Justice Perspectives Special Interest Group, recent curricular research examining published curriculum lists and course descriptions have reported no evidence of critical or social justice approaches to HRD being taught (Lim & Rager, ; Lim, Song, Choi, & Kim, ; Zachmeier, Cho, & Kim, ). Given the need for HRD to address social injustice (Byrd, ) and the negative data regarding social justice curricular content found in earlier studies, the HRD community must assess the degree to which we are preparing students to work for justice within their specific HRD contexts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More than business or accounting, HRD-like evaluation-is a field of study and practice, and is a discipline still defining itself (Stewart & Sambrook, 2012;Worthen, 1999;Zachmeier, Cho, & Kim, 2014). Pedagogical diversity in HRD in the United States echoes evaluation.…”
Section: Human Resource Developmentmentioning
confidence: 99%
“…And although a growing number of business education programs are becoming accredited due to international competition, many are still not (Trapnell & Williams, ). A 2003 attempt to establish an accreditation system for HRD in the United States “died on the vine,” with its defunct Internet site (http://www.hrdaa.org) last updated in 2007 (Zachmeier, Cho, & Kim, , p. 14).…”
mentioning
confidence: 99%